More than Copycat Television: Format Adaptation as Performance - Navarro, Vinicius (Global Television Formats: Understanding Television Across Borders, 2012)
As a trend that captured the imagination of Brazilian audiences, the rapid proliferation of dance competitions on network television is meaningful not simply as a domestic phenomenon but also, and particularly, as an illustration of the mechanisms that enable the global popularity of formatted programs. While the shows were locally produced and relied on local talent, they were all based on formats that originated elsewhere, “imported ideas” that were recycled by Brazilian producers. References to foreign versions of the formats were also part of the discourses through which the domestic adaptations were described. As one show followed the other, they invited comparisons not only among themselves but also with their international counterparts. Yet, despite the association with foreign TV shows, the formats were easily incorporated to Brazil’s television culture, a feat that could surprise neither critics nor the industry.
Keywords: 1-TV; 2-Analyses formalistes; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Brésil (corpus analysé); _Nettoyé; États-Unis (lieu de production du savoir)

The Social and Political Dimensions of Global Television Formats: Reality Television in Lebanon and Saudi Arabia - Kraidy, Marwan (Global Television Formats: Understanding Television Across Borders, 2012)
When scholars and policy makers contemplate the Arab “media revolution,” they mostly think of Al-Jazeera and its news competitors. They are guided by the assumption that all-news satellite television networks are the predominant, even the single, shaper of the Arab public sphere, a perspective exacerbated by the September 11, 2001 attacks. Drawing on a larger work (Kraidy, 2009, forthcoming), this chapter presents an alternative view, emphasizing instead the combined impact of Arab entertainment television and small media such as mobile phones on Arab governance. It explores how entertainment television is an active contributor to shaping what Arab publics discuss and do in both the social and political realms. As local (in this case regional/pan-Arab, reaching two dozen Arabic-speaking countries) adaptations of global television formats, Arab reality television shows exhibit a combination of signs and practices from several worldviews. As such, this chapter will show how Arab reality shows are open to multiple processes of appropriation and redeployment. Though numerous scholars have for years studied the differentiated “reception” of television texts in various contexts, this chapter focuses speciﬁcally on television formats in a context of growing media convergence and protracted political instability and social upheaval. Speciﬁcally, it focuses on reality television’s social and political impact, which stems primarily from its activation of new communication processes between a variety of information and media technologies creating what I call “hypermedia space.” In the new Arab information order, reality television activates hypermedia space because it promotes participatory practices like voting, campaigning and alliance building, via mobile telephones and related devices.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; Arabie Saoudite (corpus analysé); Liban (corpus analysé); Qatar (lieu de production du savoir); _Nettoyé

A Revolution in Television and a Great Leap Forward for Innovation?: China in the Global Television Format Business - Keane, Michael (Global Television Formats : Circulating Culture, Producing Identity, 2012)
Livre : For decades, television scholars have viewed global television through the lens of cultural imperialism, focusing primarily on programs produced in the US and UK markets and exported to foreign markets. This book explores how, thanks to recent technological innovation and globalization, television is now finally becoming truly global. Global Television Formats aims to revise the place of the global in television studies. The essays gathered here explore the diversity of global programming and approaches, and ask how to theorize contemporary
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Chine (corpus analysé); _Nettoyé